The Courses and Policy Environment of E-Commerce Development in China - Lin, Yao (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2017)
Chinas e-commerce industry has went through 21 years since Chinas first e-commerce enterprise established in 1996. With the rapid development of Internet and communication technology, e-commerce has penetrated into enterprises production and peoples life, and continued to exert its great potential when combining with traditional manufacturing industry. There is no doubt that e-commerce has greatly increased the efficiency of society functions. This paper cards the courses and policy environment of e-commerce development in China, identifies four stages for Chinas e-commerce development, which are initial stage, accelerated stage, standardization stage and globalization stage. At the same time, this paper describes three different characteristics of current Chinas e-commerce and also summarizes five policy focus for e-commerce. Based on the previous analysis and descriptions, this paper puts forward conclusions that China’s e-commerce sector will usher in a new round expansion on global scale, and the Chinese government will play a key and active role in promoting it. In addition, this paper warns these Chinas e-commerce enterprises to actively prevent unknown risk from home and abroad in their business expansion, the government ought to listen to e-commerce companies to deal with their specific difficulties.